Remineralization effects when using different methods to apply fluoride varnish in vitro - Han-Na Kim; Jin-Bom Kim; Seung-Hwa Jeong (Elsevier, 2018)
Background/purpose: Remineralization efficacy for early caries lesion may change when fluoride varnish (FV) is applied directly or indirectly to the lesion. This in vitro study compared direct and indirect remineralization efficacies of FV on artificial caries lesions and evaluated acid-resistance of lesion remineralized by FV and artificial saliva. Materials and methods: One hundred and twenty-six bovine demineralized specimens were allocated to four varnish groups (Duraphat®, EnamelPro®, MI™, and ClinproWhite™, n = 28 each) and a negative-control group (n = 14). Half of specimens from each varnish group had the FV applied and the other specimens didn't. The specimens treated and not treated with the FV were immersed together in 20 mL of artificial saliva at 37 °C for 24 h. Then the applied FV was removed carefully from the specimen, and immersion process was continued in fresh artificial saliva for 48 h. The negative-control group was immersed in artificial saliva for same time as in varnish groups. The acid resistance of remineralized specimens from varnish groups was compared to negative-control group. Vickers microhardness number (VHN) was measured to evaluate re-demineralization effect. Results: The ΔVHN was significantly higher for indirect remineralization (134.4 ± 31.5, mean ± SD) than for direct remineralization (66.8 ± 27.9). All varnish groups showed significant differences between the direct and indirect application methods. The acid resistance of remineralized specimens was higher in the all FV groups than in the negative-control. Conclusion: This in vitro study confirmed that the remineralization effect of fluoride varnishes would be higher in the vicinity than the underneath of the varnish treated surface. Keywords: Artificial caries lesion, Demineralization, Enamel, Fluoride varnish, Remineralization, Vickers hardness number